GAYA BELAJAR AUDIO VISUAL DAN KINESTETIK MELALUI VIDEO EDUKASI TERHADAP PESERTA DIDIK MADRASAH IBTIDAIYAH - Siti Nur Azizah; Afakhrul Masub Bakhtiar (Jurnal Al-Fatih, 2022)
The research aims to identify the effectiveness of audio learning styles, visual learning styles and kinesthetic learning styles through instructional videos for students. The research method used is a qualitative method of literature study. Learning styles that are in accordance with learning and according to students will make learning run effectively and well. Learning styles are divided into three, namely auditory learning styles, visual learning styles and kinesthetic learning styles, students use learning styles according to the characteristics of each individual student. Educators are required to be able to know the characteristics of students to determine learning styles in the learning process. Auditory learning styles, visual learning styles and kinesthetic learning styles can be combined into one and carried out simultaneously when learning takes place, combining auditory, visual and kinesthetic learning styles can train students' concentration because they utilize the senses of hearing, sight and touch. The combination of these three styles can be found in an education video, educators can explain these learning styles so that students are able to understand evenly the material being taught.